2019
DOI: 10.1002/maco.201810576
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and corrosion behavior of electrodeposited Zn‐TiN composite coatings

Abstract: In this paper, the pure Zn coating and Zn‐TiN composite coatings containing four different concentrations of TiN particles were prepared on the carbon steel by direct current electrodeposition. The X‐ray diffraction and scanning electron microscopy were used to study the crystal size, preferred orientation, and surface morphology of these coatings. The results show that the incorporation of TiN particles refines the crystal size of the Zn coating and results in the formation of a special surface morphology wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…40,203 Khorsand et al reported that the superhydrophobic Ni–Co coating with a micro-/nanoflower-like structure was fabricated on a copper substrate by electrodeposition, and the Ni–Co coating became superhydrophobic after exposure of the surface to air for two weeks. 204,205 Sheng et al prepared Zn–TiN composite coatings of papillary-shaped cluster structure with a length of about 4–8 μm on the steel substrate by electrodeposition, 206 and Xu et al prepared Ni–Mo–SiC–TiN nanocomposite coatings with spherical and columnar structures on an aluminum alloy via pulse electrodeposition. 207 During this electrodeposition process, the dispersed nanoscale SiC and TiN particles are adsorbed by Ni and Mo ions, which were transported to the cathode substrate.…”
Section: Preparation Methods Of Hierarchically Structured Superhydrop...mentioning
confidence: 99%
See 1 more Smart Citation
“…40,203 Khorsand et al reported that the superhydrophobic Ni–Co coating with a micro-/nanoflower-like structure was fabricated on a copper substrate by electrodeposition, and the Ni–Co coating became superhydrophobic after exposure of the surface to air for two weeks. 204,205 Sheng et al prepared Zn–TiN composite coatings of papillary-shaped cluster structure with a length of about 4–8 μm on the steel substrate by electrodeposition, 206 and Xu et al prepared Ni–Mo–SiC–TiN nanocomposite coatings with spherical and columnar structures on an aluminum alloy via pulse electrodeposition. 207 During this electrodeposition process, the dispersed nanoscale SiC and TiN particles are adsorbed by Ni and Mo ions, which were transported to the cathode substrate.…”
Section: Preparation Methods Of Hierarchically Structured Superhydrop...mentioning
confidence: 99%
“…204,205 Sheng et al prepared Zn-TiN composite coatings of papillary-shaped cluster structure with a length of about 4-8 mm on the steel substrate by electrodeposition,206 and Xu et al prepared Ni-Mo-SiC-TiN nanocomposite coatings with spherical and columnar structures on an aluminum alloy via pulse electrodeposition 207. During this electrodeposition process, the dispersed nanoscale SiC and TiN…”
mentioning
confidence: 99%
“…However, high cost and shortage of resources have become the bottleneck restricting its further development. In recent years, the preparation of cermet composite coatings on the surface of cheap materials has become a research hotspot because it can endow cheap materials with excellent properties comparable to cemented carbide [2][3][4][5][6][7][8]. There are various routes to preparing cermet composite coating.…”
Section: Introductionmentioning
confidence: 99%